Food contact surfaces’ hidden secrets and food handlers’ state of readiness - Saad, Mazni; Ong, Mohd Hanafi Azman; Osman, Noor Suzana; Abdullah, Norhidayah (Association of Malaysian Environment-Behaviour Researchers (AMER); ABRAmalaysia., 2019)
A guarantee for clean and safe food could be achieved when the standards of food hygiene at each preparation process and cooking practices are monitored and measured accordingly. This research examines the effectiveness of a self-regulatory practice in non-commercial residential establishments. The level of hygiene of cleaned food surface contacts was analysed through swab analysis. After a 24 hours incubation, the RIDA® count plates identified light blue colonies as total coliforms, demonstrating the existence of contamination across the majority of the selected food contact surfaces. This research, therefore, strongly encourage the application of a simple scientific tool to ensure accuracy and efficiency in the measurement of hygiene and sanitisation as it could affect the quality of life of the consumers.